Fascism, Liberalism and Europeanism in the Political Thought of Bertrand de Jouvenel and Alfred Fabre-Luce - Knegt, Daniel (Book collections on Project MUSE., 2017)
Despite the recent rise in studies that approach fascism as a transnational phenomenon, the links between fascism and internationalist intellectual currents have only received scant attention. This book explores the political thought of Bertrand de Jouvenel and Alfred Fabre-Luce, two French intellectuals, journalists and political writers who, from 1930 to the mid-1950s, moved between liberalism, fascism and Europeanism. Daniel Knegt argues that their longing for a united Europe was the driving force behind this ideological transformation-and that we can see in their thought the earliest stages of what would become neoliberalism.